2017
DOI: 10.1155/2017/8570502
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Radical Cholecystectomy for Primary or Incidental Early Gallbladder Cancer: The New Rules Governing the Treatment of Gallbladder Cancer

Abstract: Aim To evaluate the technical feasibility and oncologic safety of laparoscopic radical cholecystectomy (LRC) for primary or incidental early gallbladder cancer (GBC) treatment. Methods Articles reporting LRC for GBC were reviewed from the first case reported in 2010 to 2015 (129 patients). 116 patients had a preoperative diagnosis of gallbladder cancer (primary GBC). 13 patients were incidental cases (IGBC) discovered during or after a laparoscopic cholecystectomy. Results The majority of patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…One concern is that laparoscopic access has been associated with a reduced lymph node yield. Open or laparoscopic access for resection appears to have no effect on outcome in early gallbladder cancers, whereas data on the minimally invasive approach in more advanced cancers (T2 or above) are based on small series and not established as a standard approach.…”
Section: Resultsmentioning
confidence: 99%
“…One concern is that laparoscopic access has been associated with a reduced lymph node yield. Open or laparoscopic access for resection appears to have no effect on outcome in early gallbladder cancers, whereas data on the minimally invasive approach in more advanced cancers (T2 or above) are based on small series and not established as a standard approach.…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are limited studies reporting on the outcomes of MIS for GBCa, and its role remains controversial. [51718192021222324] Details of these studies have been summarised in Table 2. Of note, a recent large study from Korea demonstrated favourable long-term oncologic results in a 10-year prospective cohort study, supporting the oncologic safety of the laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…This is a unique finding because until now, the long-term prognostic significance of lymph node metastases has been analyzed in the current literature; however, our study is the first one to analyze the early postoperative effects of the advanced stages of the disease. The reported rates of postoperative mortality and morbidities ranged between 10% and 20% in various studies [6, 7]. However, these complications were observed following major abdominal surgery, and a stage-related correlation has not been done.…”
Section: Discussionmentioning
confidence: 99%